Valuasi Ekonomi Ekosistem Mangrove Di Pulau Jeflio, Distrik Mayamuk, Kabupaten Sorong - Dwi Indah Widya Yanti; Melisa Masengi (Median : Jurnal Ilmu Ilmu Eksakta, 2022)
Mangrove forest ecosystem is one of the natural resources of coastal areas that has very large functions and benefits. Economic valuation aims to provide economic value to the resources used in accordance with the real value from the community's point of view. The research was conducted on Jeflio Island, Mayamuk District. Methods of data collection using questionnaires and interviews. results Based on the research, the value of mangrove wood is Rp. 38,779,706,924; fish value Rp. 85.800.000; shrimp value Rp. 3,600,000; crab value Rp. 2,912,000; option value Rp.19,558,711; existence value Rp. 9,672,377. The total economic value of mangroves on Jeflio Island is Rp. 38,898,340,924. The utilization of the mangrove ecosystem on Jeflio Island is quite large so that the participation of related parties is needed in the management of the mangrove ecosystem.